EFFECT OF WORK MOTIVATION AND WORK ETHICS ON TEACHER PRODUCTIVITY PRIVATE VOCATIONAL SCHOOLS IN TEBET DISTRICT SOUTH JAKARTA - Yosephin Mery; - Matin; Moch Asmawi (Peneliti.net, 2018)
The purpose of this research is to know the effect of work motivation and work ethics toward Private Vocational School Teacher’s productivity at Tebet Districts in South Jakarta. The research methodology was survey method with quantitative approach and path analysis technique. The population of this research is 121 teachers.Research samples is 93 teachers were selected using simple random sampling technique. The data was obtained through questionnaires and analyzed using path analysis techniques.Based on the results of the data analysis in this research, it is concluded that: (1) the work motivation has a positive direct effect to productivity; (2) the work ethics has a positive direct effect to productivity; (3) the work motivation has a positive direct effect to work ethics.